Analysis of Human Small Nucleolar RNAs (snoRNA) and the Development of snoRNA Modulator of Gene Expression Vectors - Ono, Motoharu (The American Society for Cell Biology, 2010)
Human small nucleolar RNAs (snoRNAs) that copurify with nucleoli isolated from HeLa cells have been characterized. Novel fibrillarin-associated snoRNAs were detected that allowed the creation of a new vector system for the targeted knockdown of one or more genes in mammalian cells. The snoMEN (snoRNA modulator of gene expressioN) vector technology is based on snoRNA HBII-180C, which contains an internal sequence that can be manipulated to make it complementary to RNA targets. Gene-specific knockdowns are demonstrated for endogenous cellular proteins and for G/YFP-fusion proteins. Multiplex snoMEN vectors coexpress multiple snoRNAs in one transcript, targeted either to different genes or to different sites in the same gene. Protein replacement snoMEN vectors can express a single transcript combining cDNA for a tagged protein with introns containing cognate snoRNAs targeted to knockdown the endogenous cellular protein. We foresee applications for snoMEN vectors in basic gene expression research, target validation, and gene therapy.